ChemInform Abstract: Zirconium‐Catalyzed Direct Amide Bond Formation Between Carboxylic Esters and Amines. Issue 50 (December 2015) - Lenstra, Danny C.; Nguyen, D. Thao; Mecinovic, Jasmin
Abstract: Amidation of aliphatic or aromatic carboxylic esters with primary and secondary amines is accomplished in the presence of zirconocene dichloride as catalyst.